First-principles investigation of Fe-doped MgSiO 3-ilmenite - Stashans, A. (2012)
First principles density functional theory and generalised gradient approximation (GGA) have been exploited to investigate Fe-doped ilmenite-type MgSiO 3 mineral. Strong electron correlation effects not included in a density-functional formalism are described by a Hubbard-type on-site Coulomb repulsion (the DFTU approach). Microstructure of equilibrium geometries, electronic band structures as well as magnetic properties are computed and discussed in detail. Hartree-Fock methodology is used as an extra tool to study optical properties of the same system. For equilibrium state of the doped mineral we find zigzag-type atomic rearrangements around the Fe impurity. The inclusion of correlation effects leads to an improved description of the electronic properties. In particular, it is discovered that Fe incorporation produces local energy levels within the band-gap of the material. Using ?SCF method optical absorption energies are found to be equal to 2.2 and 2.6 eV leading to light absorption at longer wavelengths compared to the undoped MgSiO 3. Our results provide evidence on the occurrence of local magnetic moment in the region surrounding iron dopant. According to the outcomes, the Fe?Mg reaction can be described as substitutionally labile with Fe 2 complex being found in the high-spin state at low pressure MgSiO 3-ilmenite conditions. © 2012 Elsevier B.V. All rights reserved.